2003
DOI: 10.1074/jbc.m210328200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Antioxidant and Antiapoptotic Role of Omeprazole to Block Gastric Ulcer through Scavenging of Hydroxyl Radical

Abstract: The mechanism of the antiulcer effect of omeprazole was studied placing emphasis on its role to block oxidative damage and apoptosis during ulceration. Dose-response studies on gastroprotection in stress and indomethacin-induced ulcer and inhibition of pylorus ligation-induced acid secretion indicate that omeprazole significantly blocks gastric lesions at lower dose (2.5 mg/kg) without inhibiting acid secretion, suggesting an independent mechanism for its antiulcer effect. Time course studies on gastroprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
199
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(219 citation statements)
references
References 72 publications
13
199
0
5
Order By: Relevance
“…Excess ethanol also generates harmful ROS, superoxide anion, and hydroperoxy free radicals, involved in the pathogenesis of gastric mucosa (Dragland, Senoo, Wake, Holte, & Blomhoff, 2003; Huh et al., 2003; Oyagi et al., 2010). Gastric mucosa damage can be easily produced by the generation of toxic free radicals (Biswas et al., 2003; Naito et al., 1995) and disorders or decreases in gastric mucosa antioxidant defense systems have been involved in the pathogenesis and progression of gastric ulcers (Kwiecień et al., 2002). EtOH is often used to induce gastric ulcer in various model systems to study on the development of drug for human ulcerative disease (Szabo & Brown, 1987) and to evoke severe and rapid gastric damage together with administration of HCl (Alqasoumi et al., 2009; Huh et al., 2003; Lee et al., 2010; Oyagi et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Excess ethanol also generates harmful ROS, superoxide anion, and hydroperoxy free radicals, involved in the pathogenesis of gastric mucosa (Dragland, Senoo, Wake, Holte, & Blomhoff, 2003; Huh et al., 2003; Oyagi et al., 2010). Gastric mucosa damage can be easily produced by the generation of toxic free radicals (Biswas et al., 2003; Naito et al., 1995) and disorders or decreases in gastric mucosa antioxidant defense systems have been involved in the pathogenesis and progression of gastric ulcers (Kwiecień et al., 2002). EtOH is often used to induce gastric ulcer in various model systems to study on the development of drug for human ulcerative disease (Szabo & Brown, 1987) and to evoke severe and rapid gastric damage together with administration of HCl (Alqasoumi et al., 2009; Huh et al., 2003; Lee et al., 2010; Oyagi et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Gastric mucosal integrity is maintained by a dynamic process of cell death and cell proliferation. Among various factors involved in gastric mucosal lesions, oxidative damage and apoptotic cell death play significant roles in the loss of gastric mucosal integrity caused by various ulcerogens [6,25]. The generation of ROS plays a major role in the development of multiple pathologies, such as gastritis, peptic ulcerations or gastric adenocarcinoma [24,26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown alterations in the antioxidant status following ulceration, suggesting that reactive oxygen species (ROS) such as superoxide anion, hydrogen peroxide, and hydroxyl radical play a crucial role in the development of ethanol-induced ulceration in rats [6,7]. ROS induce oxidative damage in membrane lipids and proteins and deplete glutathione level in gastric ulcers [6]. Indeed, "on one hand, ethanol administration reduces mucus production, gastric mucosal blood flow, bicarbonate secretion, endogenous glutathione and prostaglandin levels, and on the other hand it increases the release of histamine, the influx of calcium ions, the generation of free radicals and the production of leukotrienes" [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If any change on the expression of GKN gene leads to the deficiency of GKN1 & GKN2, results have been reported as gastric inflammation, non-steroidal antiinflammatory (NSAID) induced mucosal injury and the development of neoplasia of gastric mucosa Nardone et al, 2008). Another factor concerned with the pathogenesis of NSAID-induced gastric disorder is peroxidation of lipids of cell membranes and damage to the cellular proteins by the formation of oxidative free radicals and proteases from activated neutrophils (Biswas et al, 2003). NSAIDs acts on mitochondria and uncoupling effect on oxidative phosphorylation, disperse the mitochondrial transmembrane potential and induce mitochondrial permeability transition pore (Yoshida et al, 1992;Tomoda et al, 1994;Mahmud et al, 1996;Mingatto et al, 2000;Davies et al, 2000;Ulutas et al, 2006) leading to the release of cytochrome c from mitochondrial intermembranous space into cytosol.…”
Section: Etiopathogenesis Of Gastritis and Peptic Ulcer Diseasesmentioning
confidence: 99%